MANAJEMEN PENDIDIKAN KARAKTER PESERTA DIDIK DI SMK NEGERI 1 KOLAKA - laharini laharini; Muhammad Zakariah; Rina Nur Afifa (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In the management of the character building of students carried out by the management of these educational institutions, by providing policies, namely every morning to read the Koran and read Asmaul Husna before the lesson begins, during the day the dhuhur prayer is carried out in congregation at the mosque of SMK Negeri 1 Kolaka, and the application of Islamic culture such as shaking hands when meeting teachers, smiling, appreciating guests and Islamic studies activities. Meanwhile, for students of different religions such as Christianity, Catholicism, and Hinduism, they adjust themselves according to their religious teachings. Based on the above background, and to find out the student character education management system implemented by the management of these educational institutions, the authors are interested in submitting a research thesis entitled: